A systematic review of the efficacy of live attenuated influenza vaccine upon revaccination of children - Caspard, Herve (Hum Vaccin Immunother, 2016)
Four randomized, double-blind, placebo-controlled studies in 6090 children that investigated the efficacy of live attenuated influenza vaccine (LAIV) upon revaccination of children against laboratory-confirmed cases of influenza in consecutive seasons were reviewed. The efficacy in season 2 of LAIV administered over 2 consecutive seasons was 86.7% (95 % CI: 76.8%, 92.4%) against strains antigenically similar to those contained in the vaccine. The additional efficacy of LAIV administered in season 2 compared to LAIV recipients in season 1 only was 58.4% (28.3%, 75.9%). LAIV administered over 2 consecutive seasons also was more efficacious than was LAIV administered in season 2 only (relative efficacy: 53.9% [17.4%, 74.3%]). Residual efficacy of LAIV administered in season 1 only compared to placebo administered in two consecutive seasons was 56.4% (37.0%, 69.8%). This review did not find any evidence of decreasing efficacy of LAIV when administered during 2 consecutive seasons.